Application of Blockchain Technology for Digital Transaction Security on Business Incubator Websites - Herliana Wahyu Maharani (IAIC International Conference Series, 2020)
The application of Blockchain technology in the context of providing security for transactions in the digital era 4.0 to prevent manipulation of transaction recording reports by irresponsible parties. By using research methods 10 (ten) literature reviews and methods of formulating problems, designing research, collecting data, processing & presenting data, analysis & research reports are expected to solve security problems in transactions. At present security in transactions is still very minimal, therefore a blockchain technology is needed to secure transactions where data can still be manipulated. Specifically, there are 2 (two) benefits of this research that use blockchain technology, (1) transactions become safer in the presence of encryption codes, (2) transactions become more transparent with blockchain. This research implements the encryption code into the payment system using AI Coin, where payment is now cashless, to make it more secure and transparent in transactions.